2020
DOI: 10.21037/tau-19-808
|View full text |Cite
|
Sign up to set email alerts
|

Association between sodium intake and lower urinary tract symptoms: does less sodium intake have a favorable effect or not?

Abstract: Background: Sodium intake is known to be related with hypertension (HTN), which could impact lower urinary tracts symptoms (LUTS) indirectly. To date, only limited clinical evidences exist upon the association between sodium preference and LUTS. This cross-sectional study analyzed the association between sodium preference and the severity of LUTS in men.Methods: A cross-sectional analysis has been performed and a total of 86,637 participants among total registered population of 229,226 in Korean Community Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The International Prostate Symptom Score (IPSS) applied in our previous work confirmed that sodium intake and storage symptom were correlated in male [ 12 ]. More specifically, unlike the group with neutral sodium predilection, the group with a predilection for salty taste demonstrated a significant correlation not only with elevated IPSS total score (Coef = 0.31; 95% CI: 0.27, 0.35), but also heightened risk of serious IPSS grade (OR = 1.46; 95% CI:1.35, 1.57), heightened IPSS voiding score (Coef = 0.38; 95% CI: 0.32, 0.44), heightened IPSS storage score (Coef = 0.25; 95% CI: 0.22, 0.29), as well as being more likely to develop symptoms of IPSS nocturia (OR = 1.21; 95% CI:1.16, 1.27).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The International Prostate Symptom Score (IPSS) applied in our previous work confirmed that sodium intake and storage symptom were correlated in male [ 12 ]. More specifically, unlike the group with neutral sodium predilection, the group with a predilection for salty taste demonstrated a significant correlation not only with elevated IPSS total score (Coef = 0.31; 95% CI: 0.27, 0.35), but also heightened risk of serious IPSS grade (OR = 1.46; 95% CI:1.35, 1.57), heightened IPSS voiding score (Coef = 0.38; 95% CI: 0.32, 0.44), heightened IPSS storage score (Coef = 0.25; 95% CI: 0.22, 0.29), as well as being more likely to develop symptoms of IPSS nocturia (OR = 1.21; 95% CI:1.16, 1.27).…”
Section: Discussionmentioning
confidence: 73%
“…A possible correlation between sodium intake and LUTS, particularly overactive bladder (OAB) and other storage symptoms, has been signalled by earlier our research [ 12 ]. Moreover, evidence has been produced regarding a close association between a predilection for salty taste and LUTS, such as voiding and storage symptoms and nocturia, with sodium being a risk factor for LUTS seriousness in both excessive and deficient amount [ 12 ]. However, this correlation has so far not been investigated in the case of female subjects.…”
Section: Introductionmentioning
confidence: 84%